Методы контроля биоэлектрической активности различных участков мозга - Мащенко, Татьяна Георгиевна; Борченко, Е. А. (НТУ "ХПИ", 2007)
Метод комп’ютерного електроенцефалографічного дослідження головного мозку відноситься до неінвазивних методів функціональної діагностики ЦНС й дозволяє виявляти більшість захворювань ЦНС на ранніх стадіях розвитку. В сучасній комп’ютерній функціональній діагностиці ЦНС існує безліч перспектив та переваг, але ж багато й не розв’язаних проблем. Серед них значну роль відіграють проблеми методології діагностування та обробки данних. Але найбільш складною є проблема якості зйому та реєстрації ЕЕГ сигналів.

The method of computer encephalographic investigations of encephalon is one of uninvasing methods of functional diagnostics of Central Nerval System (CNS). This method permits to explore many CNS diseases at its' start stages, some of these diseases can be explored by this method only. The present-day computer functional diagnostics of CNS has a lot of outlooks and advantages, but also it has enough unsettled problems. Among them the problems at methodology of diagnostics and machining the data have a ponderable part. But the most complicated and timetaking problem is the problem of quality pickup and registering electroencephalographic signals.
Keywords: электроэнцефалография; нервные элементы; исследования; электроды; диагностика; ритмы